Need Analysis Of ESP Material for Fish Hatchery Technology Students - Andi Musdalifah; Yuliana A; Musrina; Heriyanti (Universitas Muhammadiyah Sorong, 2023)
Abstract The procedure for choosing teaching materials consists of deciding on, modifying, and assessing instruction based on the unique needs of the learner. This study's objective is to offer the highest-quality English material feasible for Fish Hatchery Technology students of Politeknik Bombana. This study is carried out in Politeknik Bombana. 75 students and 5 lecturers of the Fish Hatchery Technology study program are participating. The information is presented as qualitative data gathered from an interview with students and lecturers as well as a questionnaire that covered relevant subjects and instructional strategies. The results show Fish Hatchery Technology’s students’ need for ESP in a broad range of subjects. The most popular subjects include fisheries entrepreneurship, fish anatomy, and the physiology of fish and their reproduction. Additionally, from the lecturers' viewpoint, they believe that students' communication and writing abilities need to be well-developed in order to support their profession and advance their careers as fish hatchery experts, fish hatchery managers, fish hatchery supervisors, laboratory analysts, nutrition and fish feed specialist, etc. The analysis of the conclusion highlights the significance of ESP for students studying fish hatchery technology. Keywords: ESP, Need Analysis, Fish Hatchery Technology